High pretreatment plasma Epstein‐Barr virus (EBV) DNA level is a poor prognostic marker in HIV‐associated, EBV‐negative diffuse large B‐cell lymphoma in Malawi. (29th November 2019) - Montgomery, Nathan D.; Randall, Cara; Painschab, Matthew; Seguin, Ryan; Kaimila, Bongani; Kasonkanji, Edwards; Zuze, Takondwa; Krysiak, Robert; Sanders, Marcia K.; Elliott, Avian; Miller, Melissa B.; Kampani, Coxcilly; et al.
Abstract: Plasma Epstein‐Barr virus (EBV) DNA measurement has established prognostic utility in EBV‐driven lymphomas, where it serves as a circulating tumor DNA marker. The value of plasma EBV measurement may be amplified in sub‐Saharan Africa (SSA), where advanced imaging and molecular technologies for risk stratification are not typically available. However, its utility in diffuse large B‐cell lymphoma (DLBCL) is less certain, given that only a subset of DLBCLs are EBV‐positive. To explore this possibility, we measured plasma EBV DNA at diagnosis in a cohort of patients with DLBCL in Malawi. High plasma EBV DNA at diagnosis (≥3.0 log10 copies/mL) was associated with decreased overall survival (OS) ( P = .048). When stratified by HIV status, the prognostic utility of baseline plasma EBV DNA level was restricted to HIV‐positive patients. Unexpectedly, most HIV‐positive patients with high plasma EBV DNA at diagnosis had EBV‐negative lymphomas, as confirmed by multiple methods. Even in these HIV‐positive patients with EBV‐negative DLBCL, high plasma EBV DNA remained associated with shorter OS ( P = .014). These results suggest that EBV reactivation in nontumor cells is a poor prognostic finding even in HIV‐positive patients with convincingly EBV‐negative DLBCL, extending the potential utility of EBV measurement as a valuable and implementable prognostic marker in SSA. Abstract : In a cohort of HIV‐positive patients with diffuse large B‐cell lymphoma (DLBCL) in Malawi, we demonstrate that high plasma Epstein‐Barr virus (EBV) DNA level at diagnosis (≥3.0 log10 copies/mL) is associated with decreased overall survival. Notably, even in those HIV‐positive patients with EBV‐negative tumors, high plasma EBV DNA remained associated with shorter survival. These results suggest that EBV reactivation in nontumor cells is a poor prognostic finding in HIV‐positive patients with EBV‐negative DLBCL.